Crystallization and Biological Studies of Nypa fruticans Wurmb Sap - Sukairi A. Hafizi; Asaruddin M. Razip; Wan S. W. M. Aliana; Wan Y. S. A. Tarmizi (Indonesian Journal of Pharmaceutical Science and Technology, 2018)
Nypa fruticans is a standout amongst the most broadly appropriated and helpful palm in the mangrove backwoods in the Southeast Asia. The sap of this plant is produced at the fruit stalks or called as ower stalks or in orescence. Nipa sap contains a lot of chemical constituents that can be used other alter- native to produce sugar that give a lot bene ts. The crystallization process of this sap was conducted in controlled temperature, pressure and humidity. As the crystal formed, remaining liquid was tested for biological studies which are antidiabetic, antioxidant and toxicity test. The antidiabetic properties were determined by inhibition of α-amylase and the result was compared to the synthetic drug which is acarbose. The sample showed that a high property of antidiabetic (50 mg/mL= 78.50% inhibition) compared to the acarbose (50 mg/mL= 80.90% inhibition). Meanwhile, the antioxidant properties of the sample were determined by2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity. The sample also showed a positive result which is EC50 112.90 mg/mL. Lastly, the toxicity test was tested to brine shrimp (Artemia salina) to get the LC50. The result (LC50=271.7 mg/mL) showed low toxic- ity at different concentration of the sample. From this study, the sample had potential antioxidant and antidiabetic properties, with low toxicity. Key words: α-amylase, antioxidant, Artemia salina, Nypa fruticans, toxicity test